An evaluation of the impact of rehabilitation on the quality of life in patients after cerebral stroke - Jędrych, Marian; Kulik, Teresa B.; Jędrych, Tomasz; Barańska, Agnieszka; Kanecki, Krzysztof; Bogdan, Magdalena; Kmieć, Paweł (Journal of Education, Health and Sport, 2018)
Cerebral stroke is the third most frequent cause of death in the human population, and one of leading causes of long-lasting disability. Medical rehabilitation has proven to be an indispensable element in stroke management. The aim of this study is to evaluate the quality of life in patients after a cerebral stroke, before and after rehabilitation. This analysis was based on data obtained from an empirical study conducted on 70 people after a stroke. The research was performed with the use of an original survey questionnaire. Due to their conditions, respondents perceived varying degrees and extents of changes in their organisms and environments pertaining to their physical, psychological, social, and professional spheres of life. In the vast majority of the patients, applied rehabilitation had a positive influence on their quality of life. There was an improvement in their physical and psychological conditions, as well as in various other aspects of life, while the intensity of emerging disorders decreased.